Az infláció leküzdésének nem kormányzati módszerei (Szociológiai Szemle, 2024)
This paper, originally presented at the November 1, 1990 session of the Social Science Society, attempts an economic sociological analysis of inflation averting behaviours undertaken by households and enterprises. This behaviour is interpreted as a process of adaptation in which economic actors acquire income exceeding their inflationary losses. The increase of nominal income, market switch, growing indebtedness, investments in hard currencies and precious metals and stocks, and the delay of large purchases are interpreted as tactics which circumvent or combat inflationary effects. It is demonstrated by listing several examples that some of these methods were effectively implemented to counterbalance inflation in some businesses and households. Yet their combined effect - with the exception of the market switch - does not reduce inflation; on the contrary, it drives the rate and effects of inflation up. The government has limited means at its disposal to influence the inflationary trends and even less the inflation averting strategies used by énterprises and households.